THE EFFECT OF TASTE AND PRICE ON SATISFACTION CONSUMERS USERS OF ELECTRIC CIGARETTES (VAPE) - Benhart Nainggolan (PT Inovasi Pratama Internasional, 2022)
This study aims to determine and analyze how big the influence of taste and price on consumer satisfaction of e-cigarette users. The analytical method used is the method of multiple linear regression ( multi linear regression ). The results showed that the multiple regression equation with two independent variables and one dependent variable showed that: Y = 8.418 + 0.569 X 1 + 0.105 X 2 it means that consumer satisfaction of electric cigarettes (Vape) (Case Study on STIE Bina Karya Tebing Tinggi students is influenced by the Taste and Price Variables. The results of the analysis also obtain a coefficient of determination (R2 ) value of adjusted R square of 0.258 or 25.8%. From From the description it can be seen that t count ( 3.524 ) > t table ( 2.045 ), as well as the significance value of 0.001 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Taste Variable (X1) has an effect on the Customer satisfaction variable (Y). This is obtained from the calculated F value equal to With = 5%, dk numerator : 2, dk denominator : 31-2-1 (5%; 2; 28) the F table value is 3,340. From this description, it can be seen that F arithmetic ( 6.218 ) > F table ( 3.340 ), and a significance value of 0.006 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Taste Variable (X1) and Price Variable (X2) have a joint effect.